The use of Analytical Geometry to obtain large areas (Research, Society and Development, 2022)
This research deals with obtaining the calculation of large areas, through google maps, where it is important to know the value of the space used by the terrain under observation. Note that the regions are not perfect plane figures, and for that, analytical geometry was used, specifically the area of a polygon. The objective of this work was to compare the value of the disclosed area of the Parque do Utinga region, located in the city of Belém Pará. It was used as a methodology, with a quantitative approach making use of the printed map, extracted from google maps, on a scale of 1.08 cm for every 500 meters, using the polygon area relationship. As a result, it was highlighted that the area disclosed by the City Hall of Belém is 13.93 km² and the calculated area was 14.06 km², presenting an error of less than 1% of the value of the area, contributing to an effective, alternative measurement of large areas.